Menggali Dampak Interaksi Digital terhadap Evolusi Sosial pada Generasi Z Kota Salatiga - Kiswara, Daru; Wahyudi, Alvianto U; Yanuartha, Rizki Amalia (Jurnal Ilmiah Widya Sosiopolitika, 2025)
Understanding the impact of digital interactions on the social evolution of Generation Z is essential, as this demographic group is poised to become the backbone of society in the coming years. This research aims to explore the influence of digital interactions on the social lives of Generation Z. A quantitative approach was employed, utilizing a purposive sampling method to select a sample of 391 respondents from Generation Z residing in Salatiga City. Data were gathered through a structured questionnaire and analyzed using simple regression analysis, processed with SPSS version 24.The findings indicate that digital interactions have a significant impact on the social evolution of Generation Z in Salatiga City. These interactions influence various dimensions of their social lives, including lifestyle shifts, changes in educational patterns, modifications in thought processes, and behavioral adjustments. The statistical analysis supports these conclusions, highlighting a significant correlation between digital interactions and these aspects of social evolution. This research underscores the pivotal role of digital interactions in shaping the social landscape of Generation Z, providing valuable insights into their evolving social dynamics.